2010
DOI: 10.1016/j.clim.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonality, impaired class switch and B-cell memory responses in WHIM syndrome

Abstract: Heterozygous truncating mutations in CXCR4 have been identified as a cause of WHIM syndrome (warts, hypogammaglobulinemia, immunodeficiency and myelokathexis). The receptor truncations have been proposed to lead to altered lymphocyte trafficking. The purpose of the described studies was to characterize the B-cell repertoire in WHIM subjects. We confirmed profound B-cell lymphopenia and demonstrated oligoclonality of the circulating B-cell pool by HCDR3 spectratyping. The response to immunization was studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 48 publications
4
57
0
3
Order By: Relevance
“…30,31 Vaccination studies have identified effector memory T cells in mouse bone marrow that may serve as a reservoir, 32,33 and this may also be true in humans. 34 Thus, bone marrow is potentially a major source of all the major cell types mobilized to the blood by plerixafor.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Vaccination studies have identified effector memory T cells in mouse bone marrow that may serve as a reservoir, 32,33 and this may also be true in humans. 34 Thus, bone marrow is potentially a major source of all the major cell types mobilized to the blood by plerixafor.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it has been proposed that the bone marrow microenvironment may be a target for new therapeutic agents in the treatment of myeloma. 6,7 Supporting this idea, Ghobrial and colleagues have previously demonstrated that targeting of CXCR4 with AMD3100-altered myeloma homing to the bone marrow, increased circulating myeloma cells, and increased sensitivity to cytotoxic agents. 8,9 These and other studies examining the CXCL12/CXCR4 axis have resulted in ongoing clinical trials.…”
Section: Kenneth Shain Moffitt Cancer Centermentioning
confidence: 80%
“…In this regard, there are several reports of short-lived antibody responses to vaccines and vaccination failures in WHIM patients. 6 Importantly, the CXCR4 1013 knock-in mouse will now allow systematic modeling of primary and memory vaccine responses, germinal center formation, and the relative importance of lymphoid versus myeloid defects to infection susceptibility in WHIM syndrome.…”
Section: Unexpected Developments In Immune Organs In Whim Syndrome --mentioning
confidence: 99%
“…Despite normal immunoglobulin levels or a mild reduction in the immunoglobulin levels, WHIM subjects display B-cell lymphopenia with a reduced number of switched memory (CD27 1 ) B cells and B-cell oligoclonality, likely contributing to infection. 5,35 Moreover, the inefficient plasma cell differentiation and maintenance that was shown in mice may account for the defective humoral immunity observed in WHIM patients. 36 Indications for the use of immunoglobulin therapy for WHIM Since the detection of hypogammaglobulinemia, WHIM patients have often been started with monthly intravenous (IVIG) or weekly subcutaneous immunoglobulin therapies, even though this symptomatic treatment is expensive, requires good patient adherence, and has an efficacy that has not been properly proved (Figure 3).…”
Section: Treatment Of Hypogammaglobulinemiamentioning
confidence: 99%
“…46 Overall, these observations and the evidence that complications of any kind have never been reported with live vaccines, such as the varicella vaccine and Bacillus Calmette-Guérin (BCG) vaccine, in patients diagnosed after vaccination, suggest that HPV vaccines may be routinely used as early prophylactic treatment of young WHIM patients. Meanwhile, it has to be considered that the long-term efficacy of vaccines is reduced in WHIM patients because of defective development or maintenance of memory B cells 35 and the early decline of an antibody response against vaccine antigens.…”
Section: Current Feasible Treatment Of Warts and Hpv Lesionsmentioning
confidence: 99%